Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Petite histoire du nationalisme Québécois et de ses racines orientalistes - Larochelle, Catherine (Modération ou extrémisme? : regards critiques sur la loi 21, 2020)
La place qu'occupe la religion dans l'espace public suscite depuis plusieurs années des débats difficiles dans la société québécoise. La Loi sur la laïcité de l'État, adoptée hâtivement par le gouvernement de la CAQ en 2019, en est la plus récente illustration. Tant par son contenu que par le processus de son adoption, la Loi 21 a provoqué des réactions passionnées. Mais que veut dire vivre et réguler la religion au quotidien au Québec à l'aune de la Loi sur la laïcité de l'État? C'est là la question à laquelle les 15 essais réunis ici tentent de répondre en examinant de façon critique les choix politiques faits par le gouvernement Legault et leurs conséquences immédiates et possibles. À partir de disciplines et de perspectives théoriques différentes, les auteurs et autrices proposent un arsenal argumentatif dont l'objectif premier est de déconstruire les raisons invoquées par le gouvernement Legault en faveur de la Loi sur la laïcité de l'État . Il apporte ainsi une contribution essentielle à un débat qui est loin d'être clos.
Section: xi, 257 pages ; 23 cm.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; cours; discipline; droits des femmes*; fem3400; histoire et politique; nationalisme; pol5480; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques